Hemorrhage-Control Training in Medical Education. (November 2020) - Gowen, Jared T; Sexton, Kevin W; Thrush, Carol; Privratsky, Anna; Beck, William C; Taylor, John R; Davis, Ben; Kimbrough, Mary K; Jensen, Hanna K; Robertson, Ronald D; Bhavaraju, Avi
Objectives: To evaluate and analyze the efficacy of implementation of hemorrhage-control training into the formal medical school curriculum. We predict this training will increase the comfort and confidence levels of students with controlling major hemorrhage and they will find this a valuable skill set for medical and other healthcare professional students. Methods: After IRB and institutional approval was obtained, hemorrhage-control education was incorporated into the surgery clerkship curriculum for 96 third-year medical students at the University of Arkansas for Medical Sciences using the national Stop The Bleed program. Using a prospective study design, participants completed pre- and post-training surveys to gauge prior experiences and comfort levels with controlling hemorrhage and confidence levels with the techniques taught. Course participation was mandatory; survey completion was optional. The investigators were blinded as to the individual student's survey responses. A knowledge quiz was completed following the training. Results: Implementation of STB training resulted in a significant increase in comfort and confidence among students with all hemorrhage-control techniques. There was also a significant difference in students' perceptions of the importance of this training for physicians and other allied health professionals. Conclusion: Hemorrhage-control training can be effectively incorporated into the formal medical school curriculum via a single 2-hour Stop The Bleed course, increasing students' comfort level and confidence with controlling major traumatic bleeding. Students value this training and feel it is a beneficial addition to their education. We believe this should be a standard part of undergraduate medical education.